Kemitraan Pemerintah Daerah dan Lembaga Swadaya Masyarakat Dalam Pengelolaan Rumah Hati Rumah Bakat di Kota Makassar - Nur Ikhsan; St Nurmaeta; Hamdan Hamdan (Publik : (Jurnal Ilmu Administrasi), 2016)
The article discusses the partnership of local governments and non- governmental Organization in the Management of the House of Talent Homes in the City of Makassar. This type of research is qualitative where data is collected by observation, interview, and documentation and then analyzed descriptively qualitative. The informants in this study were 8 people. Partnership process carried out by the Office of Social Affairs and Non-Govermental Organization. In managing home of talent homes through sereval stages of partnership patterns, namely caunter-productive predictions, where there is a bad communication that is constrained in educating Street Children, then a semi-productive partnership where the partnership pattern still seen carrying out their respective roles and function, the partnership aims to Educate persons with Social Welfare Problems to become trained and skilled social agents through sereval stages of partnership patterns to produce productive partnerships Artikel ini membahas tentang Kemitraan Pemerintah Daerah dan Lembaga Swadaya Masyrakat Dalam Pengelolaan Rumah Hati Rumah Bakat Dikota Makassar, jenis penelitian ini adalah kualitatif dimana data dikumpulkan dengan metode observasi, wawancara, dan dokumentasi kemudian dianalisis secara deskriptif kualitatif. Informan dalam penelitian ini 8 orang. Peroses kemitraan yang dilakukan Dinas Sosial dan Lembaga Swadaya Masyarakat, dalam pengelolaan Rumah Hati Rumah Bakat melalui beberapa tahapan pola kemitraan yaitu kemiraan kontra produktif, dimana pada terjadi sebuh komunikasi yang kurang baik sehingga terkendala dalam mendidik Anak Jalanan, selanjutnya kemitraan semi produktif yang dimana pola kemitraan masih terlihat menjalankan peran dan fungsinya masing-masing,, Kemitraan bertujuan untuk Mendidik Penyandang Masalah Kesejahteraan Sosial agar menjadi agen sosial yang terlatih dan terampil melalui beberapa tahap pola kemitraan sehingga menghasilkan kemitraan yang produktif.